Reduced Pain Sensation and Reduced BOLD Signal in Parietofrontal Networks during Religious Prayer - Elmholdt, Else-Marie; Skewes, Joshua; Dietz, Martin; Møller, Arne; Jensen, Martin S.; Roepstorff, Andreas; Wiech, Katja; Jensen, Troels S. (Frontiers in Human Neuroscience, 2017)
Previous studies suggest that religious prayer can alter the experience of pain via expectation mechanisms. While brain processes related to other types of top-down modulation of pain have been studied extensively, no research has been conducted on the potential effects of active religious coping. Here, we aimed at investigating the neural mechanisms during pain modulation by prayer and their dependency on the opioidergic system. Twenty-eight devout Protestants performed religious prayer and a secular contrast prayer during painful electrical stimulation in two fMRI sessions. Naloxone or saline was administered prior to scanning. Results show that pain intensity was reduced by 11% and pain unpleasantness by 26% during religious prayer compared to secular prayer. Expectancy predicted large amounts (70-89%) of the variance in pain intensity. Neuroimaging results revealed reduced neural activity during religious prayer in a large parietofrontal network relative to the secular condition. Naloxone had no significant effect on ratings or neural activity. Our results thus indicate that, under these conditions, pain modulation by prayer is not opioid-dependent. Further studies should employ an optimised design to explore whether reduced engagement of the frontoparietal system could indicate that prayer may attenuate pain through a reduction in processing of pain stimulus saliency and prefrontal control rather than through known descending pain inhibitory systems.